2017
DOI: 10.18632/oncotarget.19749
|View full text |Cite
|
Sign up to set email alerts
|

Combination of bone marrow mesenchymal stem cells sheet and platelet rich plasma for posterolateral lumbar fusion

Abstract: Bone tissue engineering provides a substitute for bone transplantation in spinal fusion. This study examined if combined bone marrow-derived mesenchymal stem cells (BMSCs) sheet with platelet-rich plasma (PRP) could promote bone regeneration in a rabbit posterolateral spinal fusion model. BMSCs was isolated and confirmed by Flow cytometric analysis and immunofluorescence staining. The morphology of BMSCs was examined by Hematoxylin and Eosin staining, scanning and transmission electron microscopy. BMSCs were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Postoperative blood loss and wound healing is the result of the synergistic effect of repairing cells, inflammatory cells, extracellular matrix, and growth factors, and is a complex process of regulating and interacting with different growth factors. [ 6 , 7 , 13 ] Studies have shown that the effect of multiple growth factors is better than that of single growth factor, which may be related to a variety of factors, which are related to multiple stages of the healing process. [ 14 , 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative blood loss and wound healing is the result of the synergistic effect of repairing cells, inflammatory cells, extracellular matrix, and growth factors, and is a complex process of regulating and interacting with different growth factors. [ 6 , 7 , 13 ] Studies have shown that the effect of multiple growth factors is better than that of single growth factor, which may be related to a variety of factors, which are related to multiple stages of the healing process. [ 14 , 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…The Pierce method was adopted to detect the concentration of total protein, and the ratio of pNPP/BCA (bicinchoninic acid) was considered as the relative value of ALP activity (Z. Liu et al, 2017).…”
Section: Alkaline Phosphatase (Alp) Stainingmentioning
confidence: 99%
“…Previously, the stem cells derived from the periosteum and bone marrow of the jaw bone (mandible) and long bone (tibia) were compared in order to determine a suitable cell source [8]. A bone marrow-derived mesenchymal stem cell sheet with platelet-rich plasma could promote bone regeneration [9]. Bone marrow is an attractive source of stem cells, but gaining stem cells from bone marrow may produce greater pain and morbidity [10].…”
Section: Characteristics Of Stem Cell Researchmentioning
confidence: 99%